2009
DOI: 10.1007/s11671-009-9299-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Tin Disulfide (SnS2) Nanowires

Abstract: The ordered tin disulfide (SnS2) nanowire arrays were first fabricated by sulfurizing the Sn nanowires, which are embedded in the nanochannels of anodic aluminum oxide (AAO) template. SnS2nanowire arrays are highly ordered and highly dense. X-ray diffraction (XRD) and corresponding selected area electron diffraction (SAED) patterns demonstrate the SnS2nanowire is hexagonal polycrystalline. The study of UV/Visible/NIR absorption shows the SnS2nanowire is a wide-band semiconductor with three band gap energies (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 21 publications
(21 reference statements)
3
39
0
Order By: Relevance
“…The thickness of each of these films was roughly on the order of 1 -2 microns. For the case with 2% tin, the film is found to be amorphous as there are no sharp peaks presented in the spectrum, but as the atomic concentration of Sn in the thin films increases, peaks assignable to either GeS 2 or SnS 2 begin to appear in the spectrum [8] [10] [11]. As the percentage of Sn increases the peaks generally become sharper and narrower, and reflect the published values for crystalline SnS 2 .…”
Section: Xrd Resultsmentioning
confidence: 93%
“…The thickness of each of these films was roughly on the order of 1 -2 microns. For the case with 2% tin, the film is found to be amorphous as there are no sharp peaks presented in the spectrum, but as the atomic concentration of Sn in the thin films increases, peaks assignable to either GeS 2 or SnS 2 begin to appear in the spectrum [8] [10] [11]. As the percentage of Sn increases the peaks generally become sharper and narrower, and reflect the published values for crystalline SnS 2 .…”
Section: Xrd Resultsmentioning
confidence: 93%
“…19,20 However there are some reports on the one dimensional SnS 2 such as nanorods, 21 nanotubes, 22 nanobelts, 23 and nanowires. 24 Intensive investigations have revealed that three dimensional structures composed by low dimensional elements have remarkably enhanced electrochemical properties compared to those composed by high-dimensional ones, owing to the nanoscale characteristics that include large surface areas, finite lateral sizes, and enhanced open edge morphologies. 23 Most of the reported three dimensional SnS 2 structures are composed by two dimensional SnS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…SnS 2 nanostructure can be a new candidate for the application in solar cell [15,16]. Up to now, few literatures have been reported using SnS 2 as anode material in DSSCs since the band gap of the as-synthesized SnS 2 is below 3 eV [17][18][19] until SnS 2 nanowires (3.3 eV) and SnS 2 crystalline nanoparticles of 15 nm (3.5 eV) are synthesized [18,20].…”
Section: Introductionmentioning
confidence: 99%